Regulation Act of Torture in Criminal Code: Opportunity and Challenge to Improve Human Rights Situation in Indonesia - M. Rizki Yudha Prawira (JUSTISI, 2025)
This research aims to analyze the opportunities and challenges with regulating the criminal act of torture in Law No. 1 of 2023 concerning the Criminal Code (KUHP). The provisions regarding the criminal act of torture in the Criminal Code certainly open up opportunities in efforts to eliminate the practice of torture in Indonesia. The provisions of Article 530 of the current Criminal Code and the explanatory section stipulate that this article directly derives from the provisions in the Convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment. On the other hand, all efforts and mechanisms to eliminate the practice of torture in Indonesia still require many steps to be taken. This research was conducted using a normative juridical method with a statutory approach. This research also provides an explanation of several gaps from previous similar studies by explaining several novel analyses, such as: (1) the application of sanctions to perpetrators must be adjusted to the provisions of international instruments, (2) revision of various articles in the Criminal Procedure Code which has the potential to perpetuate the practice of torture, and (3) the urgency to ratify the Optional Protocol to the Convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (OPCAT). The conclusion of this research is an explanation that the regulation of criminal acts of torture in the provisions of the new Criminal Code needs to be appreciated, but of course it is not enough. The state must have high commitment and political will to revise the Criminal Procedure Code openly and involve the community, ratify OPCAT, implement national legal provisions, and ensure law enforcement against perpetrators.